(untitled) (Experimental biology, 2016)
The article presents the results of a study of heavy metals concentration (Pb, Cd, Zn, Cu, Mn, Co, Ni) in the samples of the dominant land plants and soils collected in the Mangistau region. The selection of the dominant plants and soil samples was performed at three points: № 1 point (of Zhanaozen, the farm "Nurken"), number 2 point (Aktau, the farm "Bereke") and number 3 (Fort-Shevchenko, agriculture ’ Asem-Diamond "). The studied plants have unequal ability to accumulate in their tissues heavy metals. It was revealed that the best accumulative abilities among the studied plants has Artemisia terrae-albae, which in the studied areas accumulate large quantities of lead, zinc, manganese, nickel, compared with other species. And Tamarix ramosissima, Ceratocarpus arenarius characterized in that accumulates the least amount of heavy metals as compared to other plants proizrastyuschimi with them under the same environmental conditions. In all areas studied the content of heavy metals in soil samples it is within the acceptable level. However, there is a general pattern of a slight excess of the permissible level of concentration in the range of 1.09 - 1.72 to the maximum allowable concentrations for metals such as zinc, cobalt, which may be related features physiographic zones and geological factors.